PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN KETERAMPILAN PROSES SAINS UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA SMK NEGERI 3 MATARAM - Henikusniati -; Yayuk Andayani; Lalu Rudyat Telly Savalas (Postgraduate, University of Mataram, 2015)
This study aims to determine the application of science process skills to improve chemistry learning outcomes at SMK Negeri 3 Mataram. This study used a quasi-experimental design with pre-test post-test control group design. Sampling was done by using purposive sampling technique. The research sample for the experimental class were 37 students and 37 students in the control class. Data were retreived using multiple choice test that has been tested for its validity. Data were analyzed using independent sample t-test at a significance level of 0.05. N-Gain value calculation was also used to determine the chemistry learning outcome. The result showed that value of N-Gain in the experimental and control group were 0,45 and 0,42 respectively. The results showed that the science process skills approach increased students learning outcomes to medium category. The results of the t-test in both groups were shown not to be significant (α = 0.05). It can be concluded that there is no significant learning outcomes improvement of experimental group in comparison to the control group.Keywords: Science process skills, Learning outcomes